Analyzing social networks - Borgatti, Stephen P. (Sage, 2018)
Using simple language and equations, the authors provide expert, clear insight into every step of social network analysis -- including basic maths principles that even a novice can follow. Focusing on NetDraw and UCINET, the introduce relevant software tools step-by-step, in an easy to follow way. In addiiton to the fundamentals of network analysis and the research process, this edition emphasizes: digital data and social networks like Twitter; statistical models to use in SNA, like QAP and ERGM; the structure and centrality of networks; and methods for cohesive subgroups/community detection. -- Provided by publisher.